Theoretical and methodological foundations of the concepts of "Holy", "Sacred" (Eurasian Journal of Religious Studies, 2018)
The basic concepts widely used in religious phenomenology are – “holy”, “sacred”, “sacrum”. Religious phenomenology of the concept of the sacred, the holy connects with things, space, time, in words and numbers, with human activities and social practice. The concepts of the sacred, the saint occupy an important place in religious phenomenology, as in modern science there is some discrepancy in the understanding and interpretation of the given concept. Today, these concepts are studied from the standpoint of various sciences, primarily from the standpoint of religious studies, theology, sociology, culturology, psychology, there are certain developments. But as part of the Kazakhstan study, this problem has not been sufficiently studied and there are certain gaps. In connection with the current situation in the study of this issue, the identification of theoretical and methodological foundations relates to current problems in this area of research. The purpose of this article – along with such important concepts as “sacred”, “holy”, to explore and understand the “sacrum”, to show their relationship and features. The aim is also to distinguish their theological, religious study. According to the results of the research, their place and role in contemporary philosophical discourse are revealed.